Time-efficient and accurate spatial localization of automotive function architectures with function-oriented 3D visualization. Issue 4 (3rd July 2016) - Cohrs, Moritz; Kremer, Valeri; Klimke, Stefan; Zachmann, Gabriel
ABSTRACT: A primary challenge in the automotive industry is the continued increasing complexity of modern cars caused by the ever increasing amount of complex vehicle functions. These functions are implemented as mechatronic systems consisting of multiple individual components. A promising, relatively new approach to manage the increasing complexity in the development process is the function-oriented design that focuses on the interdisciplinary, holistic development of such functions. A frequent and important task in function-oriented design is the identification of the spatial distribution of the components and their connections of a specific function. In this paper, we present a very time-efficient and accurate solution to this task. Our solution uses virtual reality 3D visualization methods, based on consistent integration of function-oriented data with CAD data. We evaluated our method in several user studies and the results show that it is capable of fulfilling the task in a much more a time-efficient and more accurate way than the traditional method. GRAPHICAL ABSTRACT: